5(c+9)=5(c-4)

Simple and best practice solution for 5(c+9)=5(c-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(c+9)=5(c-4) equation:


Simplifying
5(c + 9) = 5(c + -4)

Reorder the terms:
5(9 + c) = 5(c + -4)
(9 * 5 + c * 5) = 5(c + -4)
(45 + 5c) = 5(c + -4)

Reorder the terms:
45 + 5c = 5(-4 + c)
45 + 5c = (-4 * 5 + c * 5)
45 + 5c = (-20 + 5c)

Add '-5c' to each side of the equation.
45 + 5c + -5c = -20 + 5c + -5c

Combine like terms: 5c + -5c = 0
45 + 0 = -20 + 5c + -5c
45 = -20 + 5c + -5c

Combine like terms: 5c + -5c = 0
45 = -20 + 0
45 = -20

Solving
45 = -20

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 2(1/3)x3(2/7) | | r^2-3r=2r+14 | | 2lne+3ln(x-1)=5 | | 5y-3+y+41=6y+40-2 | | 9x^2-14x-4+3x= | | x^-2=9/16 | | 24a/4 | | 19x-3=14+2x | | x^*2=9/16 | | 24a/4= | | Y=-6+3x+x^2 | | (3y+1)=23+23 | | 4xy^2z/8x^2y-4xy^2 | | 4=6-y | | -m^2+7m=0 | | [-6x-(3x+3)]=-4-[4(2x-3)-3x] | | 1.93+0.670= | | 25k^2=64 | | x^4+5=3 | | 0.25x^2+1.5x-2=0 | | x6/5=x/7 | | 6y^2+17y-28=0 | | 3s-25=-43+5s | | a^2+8a+29=12 | | 10+11c+c^2=0 | | 22/18=99/t | | -10(43)+0.35x=0.05(x-2) | | f(x)=Lnx | | (2x-3)2=16+6x | | 14/4=n/18 | | -10(43)+0.35x=(x-2) | | 4t^2-40t=-96 |

Equations solver categories